The Application of Qanun Jinayat Law in Handling Online Gambling Cases at West Aceh Syar’iyah Court Jurisdiction - Rusnan Dinata; Mohd. Din; Teuku Saiful (International Journal of Law and Society, 2025)
The phenomenon of online gambling has become a serious problem in various regions, including West Aceh Regency. data on cases handled by the West Aceh District Syar'iyah Court in the period 2021 to 2024 shows a significant increase in cases. Online gambling as part of jarimah maisir has different characteristics from conventional forms of gambling, namely digital, hidden, cross-regional, and difficult to detect by the naked eye by law enforcement officials and the general public. The problems in this study are How is the application of qanun jinayat law against online gambling offenders in the jurisdiction of the West Aceh District Syar'iyah Court, What are the obstacles faced in applying the law to online gambling offenders based on qanun jinayat law, and What are the efforts to prevent online gambling violations in the West Aceh area. This research uses empirical legal methods with a field research approach and case studies. The results showed that the application of Aceh Qanun Number 6 of 2014 concerning Jinayat Law against online gambling offenders was in accordance with the procedures of jinayat law, but its implementation was still not optimal. The Syar'iyah Court has handled a number of cases, but the number is not proportional to the potential violations. The main obstacles include limited regional authority in blocking sites, lack of digital forensic experts, absence of district-level cyber units, and weak coordination between agencies. Prevention is carried out through digital education by DISKOMINSA, thematic dakwah by the Islamic Sharia Office, as well as the Gampong Tolak Judi Online programme involving the community and the formation of the Gampong Pageu Task Force.